Judgments in preparation of financial statements of Peruvian mining companies - Castañeda Moreano, Rosa Milagros (2021)
Objective: Identify if there is a differentiated disclosure of the Peruvian mining companies’ judgments for the year 2020 in relation to the International Financial Reporting Standards (IFRS), as well as describe if there is a sufficient level of detail of the presumed assumptions in the Peruvian mining companies in 2020 in relation to the IFRS. Method: Qualitative, partially descriptive, non-experimental, transversal approach and a content analysis of the normative framework of the IFRS and the financial statements of Peruvian mining companies. Results: Four out of the eleven Peruvian mining companies do not make a differentiated disclosure of the lawsuits, and, on the other hand, the presumed assumptions are generic and do not provide greater detail. Conclusion: There is an opening of criteria in the disclosure of judgments and a lack of sufficient disclosure of the presumed assumptions.